Modelling and Fuzzy Control of an Efficient Swimming Ionic Polymer-Metal Composite Actuated Robot. (14th October 2013) - Shen, Qi; Wang, Tianmiao; Wen, Li; Liang, Jianhong
In this study, analytical techniques and fuzzy logic methods are applied to the dynamic modelling and efficient swimming control of a biomimetic robotic fish, which is actuated by an ionic polymer-metal composite (IPMC). A physical-based model for the biomimetic robotic fish is proposed. The model incorporates both the hydrodynamics of the IPMC tail and the actuation dynamics of the IPMC. The comparison of the results of the simulations and experiments shows the feasibility of the dynamic model. By using this model, we found that the harmonic control of the actuation frequency and voltage amplitude of the IPMC is a principal mechanism through which the robotic fish can obtain high thrust efficiency while swimming. The fuzzy control method, which is based on the knowledge of the IPMC fish's dynamic behaviour, successfully utilized this principal mechanism. By comparing the thrust performance of the robotic fish with other control methods via simulation, we established that the fuzzy controller was able to achieve faster acceleration compared with what could be achieved with a conventional PID controller. The thrust efficiency during a steady state was superior to that with conventional control methods. We also found that when using the fuzzy control method the robotic fish can always swim near a higher actuation frequency, which could obtain both the desired speed and high thrust efficiency.